Essays in Corporate Finance - Milanez, Anna Catherine (Harvard University, 2013)
Written in the wake of the 2007-08 financial crisis, the following essays explore the nature and implications of firm-level financial distress. The first essay examines the external effects of financial distress, while the second and third essays examine its internal consequences. The first essay investigates the potential contagion effects of financial distress among retail firms using a novel measure of retailers' geographic exposure to one another and, in particular, to liquidated chain stores. The second essay draws on new, hand-collected data on firm-level layoff instances to look into the ways in which financial distress impinges on firms' employment behavior. Building on the second essay, the third essay considers financial market reactions to layoff decisions, particularly those resulting from financial strain. Each essay sheds additional light on the ways in which financial distress propagates through to affect the economy at large. Overall, the picture that emerges is one in which firm-level financial distress appears to be an important factor behind the long and protracted nature of the current economic recovery. === Economics